DETERMINANTS OF PREMATURE SIGN-OFF WITH ETHICAL BEHAVIOR MODERATOR - Cintia Cahyati; Andry Priharta (Widya Mandala Surabaya Catholic University, 2026)
Research Purpose. This research examines the effects of auditor experience, time pressure, and materiality on early Premature sign-off, with auditor ethical behavior as a moderating variable. Research Methods. This study employed a quantitative associative approach, collecting primary data from external auditors at a South Jakarta Public Accounting Firm (KAP) using purposive sampling and analyzing them using SEM-PLS. Research Results and Findings. The study findings showed that experience had no effect, time pressure had a negative and significant effect, and materiality had a positive and significant effect on early premature sign-off, while ethical behavior could not significantly moderate the effect of the independent variables. Research Implication and Contributions. By testing the Theory of Planned Behavior in the context of premature termination of audit procedures, more specifically, by looking at the function of auditor ethical behavior as a moderating variable, this study adds to the body of knowledge on behavioral auditing. These results confirm that ethics still plays a significant role in preserving audit quality, even though they show that ethical behavior does not operate as a moderator. To reduce early premature sign-off and enhance overall audit quality, the study's practical implications for public accounting firms include strengthening the management of audit time budgets and offering training on materiality determination and professional decision-making.